Anticardiolipin antibodies in Behcet's disease: a reassessment - DİRESKENELİ, RAFİ HANER; TOKAY TARHAN, SENA (OXFORD UNIV PRESS, 2001)
Objective. To assess the frequency and clinical relevance of anticardiolipin antibodies (aCL) in Behcet's disease (BD). Methods. IgG, IgM and IgA aCL isotypes were investigated by ELISA in 128 patients with BD, 143 healthy controls and 20 systemic lupus erythematosus (SLE) patients. Results. The IgA binding index (BI) was slightly elevated in BD compared with healthy controls (120 +/- 53 vs 107 +/- 46, P = 0.02), whereas IgG and IgM aCL levels were not significantly different (IgG, BD 2.5 +/- 2.4 G phospholipid (GPL), healthy controls 2.8 +/- 3.6 GPL, P = 0.6; IgM, BD 0.7 +/- 0.9 M phospholipid (MPL), healthy controls 0.9 +/- 1.3 MPL, P = 0.6). The frequency of aCL positivity was 7% in BD (IgG 0.8%, IgM 1.6%, IgA 4.6%), 50% in SLE and 5.6% in healthy controls. IgA BI was elevated in the BLA-B5-negative group compared with HLA-B5-positive patients (P < 0.005). In a literature review, the frequency of aCL was found to be 9.5% in studies from Turkey compared with 25.5% in other series (P < 0.0001). Conclusion. These results do not suggest a primary role for aCL in BD. A significantly lower frequency of aCL in Turkish BD patients than in other series indicate that regional determinants, whether environmental or genetic, might also play a role in controlling aCL production in BD.
Keywords: autoantibodies; anticardiolipin antibodies; Behcet's disease; SYSTEMIC LUPUS-ERYTHEMATOSUS; VASCULAR COMPLICATIONS; ISOTYPE DISTRIBUTION; INVOLVEMENT; THROMBOSIS; CELLS